Rifts, orogens, cratons, and global tectonics: Introduction - S. V. Rasskazov (Геодинамика и тектонофизика, 2017)
A key role in developing the Earth theory is played by comparative studies of orogens, rifts, and platforms in the equatorial, middle and high latitudes of Asia and the adjacent Arctic regions. The modern shape of the planet’s triaxial asymmetrical cardioid ellipsoid results from its latest (Late Phanerozoic) geodynamic evolution that began in Arctic and then commenced in Asia. At this stage, mechanisms of the lithosphere extension and compression, combined with extension, were launched in Arctic and Asia, respectively. The special issue of Geodynamics & Tectonophysics presents papers on this topic.